2013
DOI: 10.1161/circresaha.112.276162
|View full text |Cite
|
Sign up to set email alerts
|

Anchored p90 Ribosomal S6 Kinase 3 Is Required for Cardiac Myocyte Hypertrophy

Abstract: Rationale Cardiac myocyte hypertrophy is the main compensatory response to chronic stress on the heart. p90 Ribosomal S6 Kinase (RSK) family members are effectors for extracellular signal-regulated kinases that induce myocyte growth. Although increased RSK activity has been observed in stressed myocytes, the functions of individual RSK family members have remained poorly defined, despite being potential therapeutic targets for cardiac disease. Objective To demonstrate that type 3 RSK (RSK3) is required for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 40 publications
(50 reference statements)
9
70
0
Order By: Relevance
“…3,4 Existing antihypertrophic therapies generally targeting membrane receptors seem to have limited efficacy 5 and lead to systemic and off target effects, 6 possibly because of nonspecific suppression of downstream signaling. 7 Identification of novel molecular regulators with pathway specificity within the intracellular hypertrophic signaling network may allow to characterize novel intervention targets for the treatment of cardiac hypertrophy and heart failure.…”
mentioning
confidence: 99%
“…3,4 Existing antihypertrophic therapies generally targeting membrane receptors seem to have limited efficacy 5 and lead to systemic and off target effects, 6 possibly because of nonspecific suppression of downstream signaling. 7 Identification of novel molecular regulators with pathway specificity within the intracellular hypertrophic signaling network may allow to characterize novel intervention targets for the treatment of cardiac hypertrophy and heart failure.…”
mentioning
confidence: 99%
“…Therefore, it has been suggested that RSK1 plays an important role in the onset of cardiac hypertrophy (Proud, 2004;Rolfe et al, 2005). However, the role of RSK1 in cardiac hypertrophy has been challenged (Fonseca et al, 2011), and a recent study has shown that RSK3 plays an important role in cardiac hypertrophy (Li et al, 2013). Regions of the hypertrophied heart are also exposed to hypoxic conditions resulting from overgrowth of cardiac tissue and insufficient blood supply (Kang and Izumo, 2000;Fortuno et al, 2001), and the chronic hypoxic condition can induce cardiomyocyte apoptosis and the loss of cells.…”
Section: Discussionmentioning
confidence: 99%
“…1D). In addition, in several articles SL0101 was used to validate the effects of BI-D1870 [10,23,28,32,34,[37][38][39][40][41][42][43][44][45][46], although unexpected differences were observed between the two inhibitors. For example, SL0101 and BI-D1870 were both observed to inhibit glucose uptake, yet by different mechanisms [23].…”
Section: Introductionmentioning
confidence: 99%